1994
DOI: 10.1902/jop.1994.65.1.56
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Prevotella intermedia and Prevotella nigrescens Isolates From Periodontic and Endodontic Infections

Abstract: The occurrence and surface properties of Prevotella intermedia and P. nigrescens in healthy sites and in periodontic and endodontic infections were studied among 73 strains, tentatively identified as P. intermedia. Fifteen strains were from necrotic root canal infections, 41 were from periodontal samples, and 17 isolates were obtained from healthy gingival sites. Identification of isolates as either P. intermedia or P. nigrescens was based on differences in malate and glutamate dehydrogenase electrophoretic mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
86
0
5

Year Published

1997
1997
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(100 citation statements)
references
References 15 publications
9
86
0
5
Order By: Relevance
“…The majority of Prevotella species in periodontally healthy subjects was P nigrescens, although those of the periodontally diseased patients in both active and healthy sites were mainly P intermedia. These results were almost consistent with the findings obtained by both Matto et al (15) and Gharbia et al (4). Matto et al concluded that the colonization of P. intermedia seemed to be more stable in periodontally diseased sites than in periodontally healthy sites, although P. intermedia and P nigrescens might occur simultaneously in the oral cavity.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The majority of Prevotella species in periodontally healthy subjects was P nigrescens, although those of the periodontally diseased patients in both active and healthy sites were mainly P intermedia. These results were almost consistent with the findings obtained by both Matto et al (15) and Gharbia et al (4). Matto et al concluded that the colonization of P. intermedia seemed to be more stable in periodontally diseased sites than in periodontally healthy sites, although P. intermedia and P nigrescens might occur simultaneously in the oral cavity.…”
Section: Discussionsupporting
confidence: 91%
“…Porphyromonas gingivalis is well known as a putative etiologic pathogen in the progression of periodontal disease, because this bacterium particularly has been associated with periodontally active diseased sites and loss of periodontal attachment (23,25,30), while black-pigmented Prevotella intermedia has been found in both periodontally diseased patients and healthy subjects (4,9,15,27,33). P. intermedia has also been reported to be associated with periapical abscess (7), pregnancy gingivitis (10), acute necrotizing ulcerative gingivitis (13) and HIV associated periodontal lesions (19).…”
mentioning
confidence: 99%
“…The four analyzed bacteria (P. nigrescens, P. intermedia, S. mutans and Actinomyces spp) were detected in a similar prevalence in samples from patients with or without black tooth stains, suggesting a similar bacterial colonization of dental biofilms of these patients. According to the literature (5,20,21), among the 13 species of Prevotella, P. nigrescens and P. intermedia are the ones most frequently found in the oral cavity. P. nigrescens is indigenous microbiota of oral cavity whereas P. intermedia is related to periodontal disease.…”
Section: Discussionmentioning
confidence: 99%
“…nigrescens, using biochemical methods and SDS-PAGE of whole cell protein analysis tentatively identified as P. intermedia in endodontic infection 11) . Baumgartner et al 12) used conventional biochemical methods and molecular biologic methods, using polymerase chain reaction of specific primers for 16S rRNA, to differentiate P.…”
Section: ⅰ Introductionmentioning
confidence: 97%